Naturally produced lovastatin modifies the histology and proteome profile of goat skeletal muscle - Leo, Teik Kee; Garba, Sani; Abubakar, Danmaigoro; Sazili, Awis Qurni; Su, Candyrine Chui Len; Jahromi, Mohammad Faseleh; Goh, Yong Meng; Ronimus, Ron; Muetzel, Stefan; Liang, Juan Boo (MDPI, 2020)
This study was conducted to examine the effects of different levels of lovastatin on the histological and sarcoplasmic proteome profile of goat skeletal muscle. A total of 20 intact male Saanen goats were randomly assigned in equal numbers to four groups and fed a total mixed ration containing 50% rice straw, 22.8% concentrates and 27.2% of various proportions of untreated or treated palm kernel cake (PKC) to achieve the target daily intake levels of 0 (Control), 2 (Low), 4 (Medium) or 6 (High) mg lovastatin/kg BW. A histological examination discovered that the longissimus thoracis et lumborum muscle of animals from the Medium and High treatment groups showed abnormalities in terms of necrosis, degeneration, interstitial space and vacuolization. Our preliminary label-free proteomics analysis demonstrates that lovastatin supplementation induced complex modifications to the protein expression patterns of the skeletal muscle of the goat which were associated with the metabolism of carbohydrate and creatine, cell growth and development processes and other metabolic processes. The changes in these biochemical processes indicate perturbations in energy metabolism, which could play a major role in the development of myopathy. In conclusion, the present study suggests that supplementation of naturally produced lovastatin above 4 mg/kg BW could adversely affecting the health and wellbeing of treated animals.